ANALYSIS CLASIFICATION FACTORS OF WORK PRODUCTIVITY AMONG TEACHERS DURING WFH (WORK FROM HOME) BASED ON DECISION TREE - Indah Lutfiya; Novelia Qothrunnada; Selvy Nur Amalia (UNUSA Press, 2021)
The COVID-19 pandemic since its inception at the end of December in China and entering Indonesia in March 2020 has had many impacts on the world of employment, including in the realm of education. The COVID-19 pandemic has also had a strong impact on work productivity. Various different backgrounds ranging from work tenure, latest education level and emotional intelligence make the level of work productivity at SMPN 1 Tembelang quite varied. This research aims to analyze the classification factors that affect teacher work productivity during WFH. The type of research used is analytic observational with a cross-sectional approach. This research was conducted at SMP Negeri 1 Tembelang Jombang with a sample of 45 people. Data analysis is done by Decision Tree. The results of the accuracy of the model testing generated from the training data to the testing data show that the accuracy value is 65.67%. The classification of high productivity levels is found in the group of teachers who have a long work tenure, mature age and high emotional intelligence. While the classification of medium productivity is dominated by groups of teachers of medium and adult age. It is recommended to conduct training and mentoring of online learning programs to improve skills and expertise for teachers, especially those who have and are classified as elderly.